Total Digestibility and Protein Digestibility of Litopenaeus Vannamei Feed Made from Moringa Oleifera Flour - Wellem H. Muskita,; Sitti Sasrani Gufana,; Agus Kurnia,; Muhaimin Hamzah,; Deki Zulkarnain,; La Ode Sahaba,; La Ode Muh. Munadi, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study aims to evaluate the overall digestibility and protein digestibility of feed containing Moringa oleifera meal in white shrimp (Litopenaeus vannamei). The research method involved using standard techniques to feed the shrimp with various concentrations of Moringa oleifera meal and measure total digestibility and protein digestibility. The results showed that the highest total digestibility was obtained in treatment C at 58,68%, while the lowest was in treatment B at 19,35%. Protein digestibility values ranged from 71,94% to 84,94%, with the highest protein digestibility found in treatment C(10% Moringa oleifera leaf meal and 10% soybean meal). These findings indicate that the Moringa oleifera meal has the potential to be an effective and sustainable alternative feed ingredient for the cultivation of Litopenaeus vannamei, provided that its processing can minimize antinutrients. Further research is needed to optimize feed formulation and processing techniques to enhance the digestibility quality of the Moringa oleifera meal.
Keywords: Total Digestibility; Protein Digestibility; Litopenaeus vannamei; Moringa oleifera